Postschool Outcomes of Youths with Deafblindness in the United States: Building Further Understandings for Future Practice. (May 2019) - Petroff, Jerry G.; Pancsofar, Nadya; Shaaban, Engy
Introduction: This study examines the postschool outcomes for youths with deafblindness, aged 18–30 years, in the areas of independent living, employment, and friendships. Methods: Survey data were collected on 80 youths with deafblindness across the United States. Data addressed postschool outcomes, in addition to youths' demographics and high school experiences. Results: The findings of this study suggest that very few youths were living independently or engaged in paid employment. Conversely, it was reported that the vast majority of youths had friends, and most youths had five or more friendships. Associations between the youths' demographics, high school experiences, and postschool outcomes show that youths with higher skills in reading and problem-solving were more apt to have been educated in inclusive secondary education settings, had access to the general education curriculum, and to have experienced positive postschool outcomes. Transition planning for these youths was not significantly associated with their postschool outcomes. Discussion: These findings are consistent with trends in previous studies regarding postschool outcomes for youths with deafblindness. Future research is needed in formal transition planning and what additional factors may need to be better understood in providing opportunities in postschool life for youths with deafblindness. Implications for practice: Findings from this study suggest better inclusion efforts are needed for students with deafblindness in terms of associated opportunities and experiences that would prepare them for paid employment and independent living, along with social engagement and friendships.